PENGEMBANGAN MATERI MANAJEMEN EMOSI SISWA SMA/SEDERAJAT - Annisa Nur Ekanantari; Rosmawati '; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research aims to develop Emotional Management necessary forhigh school students in terms of aspects of clarity, systematics, image support,freshness, completeness of the material, and support for video or games. Type ofresearch is the development of data analysis techniques using data validity. The sourceof the data obtained from the supervisor 1, supervisor 2, four teachers BK, and 38students of class XI SMAN 12 Pekanbaru. From the values given by the experts and thestudents gain calculation results for material gain clarity aspect value of 4.3 whichincludes categories Very clear, systematic aspects of the material to obtain the value of4.3 which includes categories Very Systematic, to support aspects of the image to getthe value 4.3 category that includes very good, for the renewal of the material aspectsof obtaining the value of 4.1 which includes the category of Recently, to obtain materialsufficiency aspect value of 4.3 which includes the category of Most Complete, to supportaspects of the video or games to get the value 4.4 category that includes very good,whereas for all aspects of assessment materials indicate that the materials developedalready meet the criteria expected by the acquisition value of 4.29 which includes thecategory of Very Good.Keywords: Emotional Management Material